EXTH-95. UNCOVERING THERAPEUTIC VULNERABILITIES IN MISMATCH REPAIR-DEFICIENT GLIOMAS. (14th November 2022) - Pal, Sangita; Boynton, Adam; Johnston, Ryan; Currimjee, Naomi; Qian, Kenin; Touat, Mehdi; Bellamy, Charlotte; Ho, Patricia; Root, David; Persky, Nicole; Goodale, Amy; Berstler, Jim; et al.
Abstract: Approximately 25% of recurrent gliomas exhibit hypermutation, which is most often acquired in chemotherapy sensitive gliomas post-treatment with standard of care alkylating agent temozolomide, Intriguingly, nearly all of these recurrent hypermutant tumors harbor deficiencies in mismatch repair (MMR) genes. Unlike other MMR-deficient cancers, hypermutant gliomas do not exhibit detectable microsatellite instability (MSI) at the population level, and do not share similar dependencies. Thus, strategies to therapeutically target MMR-deficient and hypermutant gliomas are urgently needed, and likely to impact many patients. To evaluate vulnerabilities associated with MMR-deficient gliomas, we have generated isogenic MMR-deficient models by systematic ablation of core MMR genes MSH2, MSH6, MLH1, and PMS2, in multiple patient-derived glioma cell lines using a robust all-in-one CRISPR-Cas9 system. We characterized these isogenic MMR-deficient glioma lines in comparison to respective MMR-proficient control line by performing differential gene expression analysis and subsequent gene set enrichment analyses. Our analyses reveal in an unbiased fashion an enrichment of several hallmark gene sets including cell cycle control and DNA repair in the MMR-deficient cell lines. We performed a CRISPR-Cas9 knockout screen in these MMR deficient and hypermutant models and identified candidate genes involved in DNA repair, cell cycle, RNA metabolism and other pathways as preferential dependencies in the MMR-deficient glioma cells. We also screened multiple MMR-deficient isogenic models against the high-throughput drug repurposing (REPO) chemical library and our preliminary results reveal a number of compounds from a variety of drug classes that selectively kill the MMR-deficient glioma cells, indicating that the loss of MMR confers differential dependencies to these small molecule inhibitors. The candidate drugs and genes identified from these high-throughput assays are currently being subjected to further validation, and they possibly will help us identify novel therapeutic strategies or improve existing therapeutic strategies to target recurrent MMR-deficient gliomas.